Growth of PbS nanopyramidal particulate films for potential applications in quantum-dot photovoltaics and nanoantennas - Hawaldar, Ranjit R.; Mulik, Uttam P.; Patil, K.; Pasricha, R.; Sathaye, S.; Lewis, A.; Amalnerkar, Dinesh P. (Materials Research Bulletin, 2005)
We report a simple interfacial process called the liquid-liquid interface reaction technique (LLIRT) that leads to the formation of nanosized PbS particulate films with hitherto unreported pyramidal morphology. The resultant PbS films were characterized by transmission electron microscopy (TEM) with selected area electron diffraction (SAED), X-ray diffractometery (XRD), atomic force microscopy (AFM), near field scanning optical microscopy (NSOM) and UV-vis spectroscopy. The pyramidal morphology is speculated to originate from the preferred orientation of the 2 2 0 plane of cubic PbS. Our nanopyramidal PbS particulate films display remarkably sharp excitonic peak centered around 656 nm that accounts for a band gap of 1.8 eV suggesting, in turn, their potential application in QD photovoltaics. Interestingly, the feasibility of such nanopyramids to potentially act as nanoantennas (as revealed by the NSOM) is also suggested. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Atomic force microscopy; Chemical synthesis; Electron microscopy; Nanostructures; Optical properties

PVA stabilized gold nanoparticles by use of unexplored albeit conventional reducing agent - Khanna, P. K.; Gokhale, R.; Subbarao, V. V. V. S.; Vishwanath, A. K.; Das, B. K.; Satyanarayana, C. V. V. (Materials Chemistry and Physics, 2005)
Poly(vinyl alcohol) (PVA) stabilized gold nanoparticles have been prepared in aqueous medium using two different reducing viz.; hydrazine hydrate, a stronger reducing agent and sodium formaldehydesulfoxylate (SFS), a slightly weaker reducing agent. SFS is used for first ever time for reduction of gold metal salt. The PVA stabilized gold nanoparticles solutions are wine red to blood red coloured and are stable over a long period of time with no indication of aggregation. The solution shows strong visible light absorptions in the range of 520-540 nm, characteristics of gold nanoparticles. Powder X-ray diffraction patterns of freshly prepared films containing gold nanoparticles indicated particles size to be about 15 nm. Transmission electron microscopy (TEM) of a more than two-week-old sample revealed well-defined non-agglomerated spherical particles of about 50 nm diameter in solutions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Nanostructures; Polymer

Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

X-ray photoelectron spectroscopic investigations of Cu2O nanoparticles - Nikesh, V. V.; Mandale, A. B.; Patil, K. R.; Mahamuni, Shailaja (Materials Research Bulletin, 2005)
Cuprous oxide nanoparticles of five different sizes were obtained by electrochemical as well as chemical routes. Various capping agents were used to passivate the nanoparticles. X-ray diffraction studies show formation of single phased, cubic Cu2O nanoparticles. X-ray photoelectron spectroscopic studies indicate formation of CuO phase on the surface of Cu2O nanoparticles for uncapped as well as for those, capped by tetraoctylammonium bromide. On the other hand polyacrylamide and polyvinyl pyrrolidone capped samples did not show presence of CuO. X-ray photoelectron spectroscopy also indicates formation of a Cu2+ complex with the capping material on the surface of Cu2O nanoparticles. The results were discussed in terms of capability of passivation of various additives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Oxides; photoelectron spectroscopy; Surfaces

Scanning tunneling microscopy/spectroscopy on Au nanoparticles assembled using lauryl amine (LAM) and octadecane thiol (ODT) - Datar, Suwarna; Chaudhary, Minakshi V.; Sastry, Murali; Dharmadhikari, C. V. (Applied Surface Science, 2007)
In this report, we demonstrate scanning tunneling microscopy and spectroscopy on thin filins of lauryl amine (LAM) and octadecane thiol (ODT) protected gold nanoparticles. We show that the zero current in the I-V curves (measure of Coulomb blockade (CB) of the nanoparticles) depends on the properties of the spacer molecule. In both the cases the gap voltage and the tunneling current at which the images are obtained are quite different which is further confirmed from the fitting performed based on the orthodox theory. The values for the capacitance and charging energy obtained from the fitting for ODT capped particles are comparable to the values obtained using spherical capacitor model. In contrast, values of these parameters were found to differ for LAM capped nanoparticles. While imaging, ODT capped nanoparticles were observed to drag along the scan direction leading to ordering of particles. Images of LAM capped gold nanoparticles show local ordering in self-assembly of particles although no evidence of large scale ordering in spatial Fourier transform was seen. These observations suggest that nanoparticles with larger CB would be intaged nonevasively in contrast to small CB systems for which tip induced effects will be dominant. In both the systems the current was found to rise faster than theoretical curves based on the orthodox theory suggesting that mechanism of charge transfer in this case may involve field emission rather than tunneling through a rectangular barrier. An attempt has been made to explain charge transfer based on Fowler-Nordheim (F-N) plots of the I-V curves. (c) 2006 Elsevier B.V All rights reserved.
Keywords: Nanostructures; scanning tunneling microscopy (STM)

Controlled synthesis of ZnO from nanospheres to micro-rods and its gas sensing studies - Navale, Shalaka C.; Gosavi, S. W.; Mulla, Imtiaz S. (Talanta, 2008)
1D ZnO rods are synthesized using less explored hydrazine method. Here we find, besides being combustible hydrazine can also be used as a structure-directing agent. The ratio of zinc nitrate (ZN) to hydrazine is found to control the morphology of ZnO. At lower concentration of ZN as compared with hydrazine the morphology of ZnO is found to be spherical. As we increase the hydrazine content the morphology changes from spherical (diameter similar to 100 nm) to the elongated structures including shapes like Y, T as well dumbbell (diameter similar to 40 nm and length similar to 150 nm). Interestingly for more than 50% of hydrazine ZnO micro-rods are formed. Such rods are of diameter similar to 120 mn having length of about 1 mu m for ZN to hydrazine ratio of 1:9, isolated as well as bundle of rods are seen in scanning electron microscopy (SEM). The X-ray diffraction (XRD) reveals the phase formation with average particle size of 37 nm as calculated using Scherrer's formula. The high-resolution transmission electron microscopy (HRTEM) is also done to confirm the d-spacing in ZnO. Gas sensing study for these samples shows high efficiency and selectivity towards LPG at all operating temperatures. Photoluminescence (PL) study for these samples is performed at room temperature to find potential application as photoelectric material. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrazine; LPG sensor; Nanostructures; photoluminescence; ZnO

Low temperature synthesis of nanocrystalline lithium ferrite by a modified citrate gel precursor method - Verma, Seema; Joy, Pattayil Alias (Materials Research Bulletin, 2008)
Single phase nanocrystalline lithium ferrite is synthesized by a modified citrate gel precursor technique. Ferrite nanoparticles of average size of 8 nm, obtained after calcination of the citrate gel Made by the usual method at 450 degrees C, show superparamagnetic behavior. However, small amounts of alpha-Fe(2)O(3) is formed as an impurity phase clue to the initial formation of some gamma-Fe(2)O(3) phase. Oil the other hand, when the pH of the mixed Solution is increased to 7 after the addition of ammonia Solution, a lower calcination temperature of 200 degrees C is sufficient for the formation of single phase lithium ferrite nanoparticles of size 30 nm. No impurity phases are detected when the nanocrystalline powders arc calcined at higher temperatures. The magnetic properties of the ferrite nanoparticles of different sizes obtained by calcining the powders at different temperatures are studied. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Nanostructures; Oxides

Natural gum reduced/stabilized gold nanoparticles for drug delivery formulations - Dhar, Sheetal; Reddy, E. Maheswara; Shiras, Anjali; Pokharkar, Varsha; Bhagavatula L. V. Prasad (Chemistry-A European Journal, 2008)
``Gellan Gum'', widely used in food and confectionary industry as a thickening and gelling agent, has been employed as a reducing and stabilizing agent for the synthesis of gold nanoparticles. These nanoparticles display greater stability to electrolyte addition and pH changes relative to the traditional citrate and borohydride reduced nanoparticles. Subsequently these have been used to load anthracycline ring antibiotic doxorubicin hydrochloride. The drug loaded on these nanoparticles showed enhanced cytotoxic effects on human glioma cell lines LN-18 and LN-229.
Keywords: Apoptosis; Cytotoxicity; drug delivery; Gold; Nanostructures; natural gums

Near-complete phase transfer of single-wall carbon nanotubes by covalent functionalization - Kakade, Bhalchandra A.; Patil, Sanjay; Sathe, Bhaskar; Gokhale, Suresh; Pillai, Vijayamohanan (Journal of Chemical Sciences, 2008)
We describe here an efficient phase transfer of single wall carbon nanotubes (SWNTs) from aqueous to non-aqueous media using a unique amide functionalization route, where water soluble SWNTs (2.6 mg/mL) are effectively transferred to solvents like chloroform, toluene and CS(2). A maximum of 30 wt% of oxygenated groups have been generated on the side walls by rapid microwave treatment, leading to a solubility of more than 2.6 mg/mL in water. Approximate surface amine coverage of 50% has been accomplished after oxalyl chloride treatment as inferred from thermogravimetry and X-ray photoelectron spectroscopy by controlling several key parameters associated with the extent of functionalization including purity of the sample, temperature and time.
Keywords: Carbon nanotubes; microscopy; Microwave; Nanostructures; solubility of SWNTs

Photocatalytic decomposition of methylene nanocrystalline titania prepared by different blue on methods - Ramaswamy, Veda; Jagtap, Neelam; Vijayanand, S.; Bhange, Deu S.; Awati, Preeti (Materials Research Bulletin, 2008)
Nanocrystalline particles of pure anatase titania were prepared by two different methods. One is the sol-gel method at ambient temperature using ultrasonication (TiO2-SG-US) and conventional stirring method (TiO2-SG-S) and the other by surfactant assisted hydrothermal synthesis (TiO2-HT). More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline titania by sol gel ultrasonication method and hydrothermal synthesis method. The behavior of anatase titania in photocatalytic decomposition of methylene blue in aqueous medium was studied as a function of the method of preparation and the crystallite size. The nanoparticles prepared by ultrasonication method were more effective than both, the sample prepared by conventional stirring method and commercial Degussa P-25. The higher photocatalytic activity of TiO2-SG-US is attributed to the more uniform size of the particles as compared to TiO2-SG-S samples. Both TEM and XRD data on TiO2-HT samples reveal a uniform and nanocrystalline TiO2 particles, which showed photocatalytic activity in both UV and visible region although brookite phase was also present. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Sol-gel chemistry

Epitaxially grown zinc-blende structured Mn doped ZnO nanoshell on ZnS nanoparticles - Limaye, Mukta V.; Singh, Shashi B.; Date, Sadgopal K.; Gholap, Ramkrishna S.; Kulkarni, Sulabha K. (Materials Research Bulletin, 2009)
Zinc oxide in the bulk as well as in the nanocrystalline form is thermodynamically stable in the wurtzite structure. However, zinc oxide in the zinc-blende structure is more useful than that in the wurtzite structure due to its superior electronic properties as well as possibility of efficient doping. Therefore, zinc oxide shell is grown epitaxially on zinc sulphide core nanoparticles having zinc-blende structure. It is shown that doping of manganese could be achieved in zinc oxide nanoshell with zinc-blende structure. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Luminescence; Nanostructures; Semiconductors; X-ray diffraction

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Microwave-assisted synthesis and humidity sensing of nanostructured alpha-Fe2O3 - Deshmukh, Rupali G.; Badadhe, Satish S.; Mulla, Imtiaz S. (Materials Research Bulletin, 2009)
Nanocrystalline alpha-Fe2O3 has been prepared on a large-scale by a facile microwave-assisted hydrothermal route from a solution of Fe(NO3)(3)center dot 9H(2)O and pentaerythritol. A systematic study of the morphology, crystallinity and oxidation state of Fe using different characterization techniques. Such as transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy was performed It reveals. that nanostructured alpha-Fe2O3 comprises bundles of nanorods with a rhombohedral crystalline Structure. The individual nanorod has 8-10 nm diameter and similar to 50 nm length. The as-prepared nanostructured alpha-Fe2O3 (sensor) gives selective response towards humidity. The sensor shows high sensitivity, fast linear response to change in the humidity with almost 100% reproducibility. The sensor works at room temperature and rejuvenates without heat treatment. The as-prepared nanostructured alpha-Fe2O3 appears to be a promising humidity sensing material with the potential for commercialization. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrical properties; Nanostructures; Oxides; X-ray diffraction

Nanocrystalline Mn-Zn-ferrite by novel oxalato-hydrazinated complex method - Kanade, K. G.; Amalnerkar, Dinesh P.; Potdar, H. S.; Kale, B. B. (Materials Chemistry and Physics, 2009)
We report here for the first time the synthesis of technologically important ferrite, using a metal oxalato-hydrazinate (MOH) complex method. The MOH complex of iron-manganese-zinc was synthesized at room temperature using the precursors, ferrous ammonium sulphate, manganese acetate and zinc acetate. Thermo-gravimetric studies of MOH intermediate showed complete phase formation of MnZnFe(2)O(4) at 280 degrees C. XRD data showed the formation of single phase cubic spinel MnZnFe(2)O(4). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) demonstrate the spherical shape particle morphology. TEM images indicated the particle size of ferrite powder in the range of 20-36 nm. Magnetization of synthesized nano-sized Mn(0.69)Zn(.0.19)Fe(2.12)O(4) was observed coercive force (H(c)) at 127.82 Oe with a saturation magnetization (M(s)), 34.5 emu g(-1) using vibrating sample magnetometer (VSM) at room temperature. Mossbauer study of nano-sized ferrite powder showed super-paramagnteic behavior. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic materials; Mn-Zn-ferrite; Nanostructures; Optical properties

On the structural, magnetic and electrical properties of sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2009)
Nanoparticles of cobalt ferrite were synthesized by sol gel method. These particles were structurally characterized by using X-Ray Diffraction and Transmission Electron Microscopy, High Resolution Transmission Electron Microscopy, Energy Dispersive Spectrum and Inductively Coupled Plasma Analysis and the results confirmed the formation of spherically shaped nanoparticles of cobalt ferrite having a size lying in the range of 13-14 nm. The as prepared sample was sintered at 800 degrees C and the structural, magnetic and dielectric properties were measured. The dielectric properties were studied and analyzed as a function of temperature and frequency. The ac and dc conductivity studies were carried out to delve into the conduction mechanism. The existing models based on quantum mechanical tunneling were effectively employed to explain the frequency dependent conductivity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic Transport; Magnetic measurements; Magnetically ordered materials; Nanostructures; Scanning and transmission electron microscopy; Sol-gel synthesis; X-ray diffraction

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures

Surface texture and specific adsorption sites of sol-gel synthesized anatase TiO2 nanoparticles - Zaki, Mohamed I.; Mekhemer, Gamal A. H.; Fouad, Nasr E.; Jagadale, Tushar C.; Ogale, Satishchandra B. (Materials Research Bulletin, 2010)
The surface properties of sot-gel synthesized anatase titania (TiO2) nanoparticles are probed by sorptiometry, infrared absorption spectroscopy, UV-vis diffuse reflectance spectroscopy and high resolution transmission electron microscopy. The results reveal strong correlations of the surface area, porosity, pyridine adsorption capacity and strength, and catalytic methylbutynol decomposition activity. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Oxides; Sol-gel chemistry; X-ray diffraction

Low temperature pH dependent synthesis of flower-like ZnO nanostructures with enhanced photocatalytic activity - Vaishampayan, Mukta V.; Mulla, Imtiaz S.; Joshi, Satyawati S. (Materials Research Bulletin, 2011)
In the present study we have synthesized flower-like ZnO nanostructures comprising of nanobelts of 20 nm width by template and surfactant free low-temperature (4 degrees C) aqueous solution route. The ZnO nanostructures exhibit flower-like morphology, having crystalline hexagonal wurtzite structure with (001) orientation. The flowers with size between 600 and 700 nm consist of ZnO units having crystallite size of similar to 40 nm. Chemical and structural characterization reveals a significant role of precursor: ligand molar ratio, pH, and temperature in the formation of single-step flower-like ZnO at low temperature. Plausible growth mechanism for the formation of flower-like structure has been discussed in detail. Photoluminescence studies confirm formation of ZnO with the defects in crystal structure. The flower-like ZnO nanostructures exhibit enhanced photochemical degradation of methylene blue (MB) with the increased concentration of ligand, indicating attribution of structural features in the photocatalytic properties. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Defects; Nanostructures; Optical properties; Semiconductor

Role of lattice defects and crystallite morphology in the UV and visible-light-induced photo-catalytic properties of combustion-prepared TiO2 - Deshpande, Aparna; Madras, Giridhar; Gupta, N. M. (Materials Chemistry and Physics, 2011)
The physico-chemical, photo-physical and micro-structural properties responsible for the strikingly different photocatalytic behavior of combustion-prepared TiO2 (c.TiO2) and Degussa P25 (d.TiO2) samples are elucidated in this study. Electron microscopy and selected area electron diffraction micrographs revealed that the two samples exhibited different morphologies. The grains of c.TiO2 were spherical and comprised of 5-6 nm size primary particle. On the other hand, d.TiO2 consisted of large (0.5-3.0 mu m) size and irregular shape aggregates having primary particles of 15-40 nm cross-sectional diameter. The ESR study revealed that the presence of certain defect states in c.TiO2 helped in stabilization of O-. and Ti3+-OH type species during room-temperature UV-irradiation. No such paramagnetic species were however formed over d.TiO2 under similar conditions. C1s and Ti 2p XPS spectra provide evidence for the presence of some lattice vacancies in c.TiO2 and also for the bulk Ti4+ -> Ti3+ conversion during its UV-irradiation. Compared to d.TiO2, c.TiO2 displayed considerably higher activity for discoloration of methyl orange but very poor activity for splitting of water, both under UV and visible light radiations. This is attributed to enhanced surface adsorption of dye molecules over c.TiO2, because of its textural features and also the presence of photo-active ion-radicals. On the other hand, the poor activity of c.TiO2 for water splitting is related to certain defect-induced inter-band charge trapping states in the close vicinity of valence and conduction bands of c.TiO2, as revealed by thermoluminescence spectroscopy. Further, the dispersion of nanosize gold particles gave rise to augmented activity of both the catalysts, particularly for water splitting. This is explained by the promotional role of Au-0 or Au-0/TiO2 interfacial sites in the adsorption and charge-adsorbate interaction processes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Band-structure; Interfaces; Microstructure; Nanostructures; Semiconductors

Room temperature ferromagnetism in undoped and Fe doped ZnO nanorods: microwave-assisted synthesis - Limaye, Mukta V.; Singh, Shashi B.; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Solid State Chemistry, 2011)
One-dimensional (1D) undoped and Fe doped ZnO nanorods of average length similar to 1 mu m and diameter similar to 50 nm have been obtained using a microwave-assisted synthesis. The magnetization (M) and coercivity (H-c) value obtained for undoped ZnO nanorods at room temperature is similar to 5 X 10(-3) emu/g and similar to 150 Oe, respectively. The Fe doped ZnO samples show significant changes in M -H loop with increasing doping concentration. Both undoped and Fe doped ZnO nanorods exhibit a Curie transition temperature (T-c) above 390 K. Electron spin resonance and Mossbauer spectra indicate the presence of ferric ions. The origin of ferromagnetism in undoped ZnO nanorods is attributed to localized electron spin moments resulting from surface defects/vacancies, where as in Fe doped samples is explained by F center exchange mechanism. (C) 2010 Published by Elsevier Inc.
Keywords: Diluted magnetic semiconductors; Nanostructures; ZnO

Electrochemical preparation of luminescent graphene quantum dots from multiwalled carbon nanotubes - Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemistry-A European Journal, 2012)
Green luminescent, graphene quantum dots (GQDs) with a uniform size of 3, 5, and 8.2(+/- 0.3) nm in diameter were prepared electrochemically from MWCNTs in propylene carbonate by using LiClO4 at 90?degrees C, whereas similar particles of 23(+/- 2) nm were obtained at 30?degrees C under identical conditions. Both these sets of GQDs displayed a remarkable quantum efficiency of 6.3 and 5.1?%, respectively. This method offers a novel strategy to synthesise size-tunable GQDs as evidenced by multiple characterisation techniques like transmission and scanning electron microscopy, atomic force microscopy, Raman spectroscopy and X-ray diffraction (XRD). Photoluminescence of these GQDs can be tailored by size variation through a systematic change in key process parameters, like diameter of carbon nanotube, electric field, concentration of supporting electrolyte and temperature. GQDs are promising candidates for a variety of applications, such as biomarkers, nanoelectronic devices and chemosensors due to their unique features, like high photostability, biocompatibility, nontoxicity and tunable solubility in water.
Keywords: electrochemical synthesis; graphene; Nanostructures; photoluminescence; quantum dots

Green synthesis of TiO2 nanoparticles by using aqueous extract of Jatropha curcas L. latex - Hudlikar, Manish; Joglekar, Shriram; Dhaygude, Mayur; Kodam, Kisan M. (Materials Letters, 2012)
Present study deals with a green synthesis of TiO2 nanoparticles by using 0.3% aqueous extract prepared from latex of Jatropha curcas L. TiO2 nanoparticles were characterized by X-ray diffraction (XRD), Selected Area Electron Diffraction (SAED), Transmission Electron Microscopy (TEM), Energy Dispersive Analysis of X-rays (EDAX) and Fourier Transform Infrared Spectroscopy (FTIR). Fourier Transform Infrared Spectroscopy (FTIR) were performed to find the role of curcain (enzyme), cyclic peptides namely curcacycline A (an octapeptide) and curcacycline B (a nonapeptide) as a possible reducing and capping agents, present in the latex of J. curcas L. The average size of TiO2 nanoparticles was found to be in the range of 25 to 100 nm. Our result shows that there are two broad categories of nanoparticles, first having diameter from 25 to 50 nm which are mostly spherical in shape and second having some larger and uneven shapes. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Electron microscopy; Fourier Transform Infrared Spectroscopy (FTIR); Nanostructures

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures

Effect of organic modification on the intercalation and the properties of poly(phenylene oxide)/polystyrene blend-clay nanocomposites - Tiwari, Rajkiran R.; Natarajan, Upendra (Journal of Thermoplastic Composite Materials, 2013)
Nanocomposites prepared by the dispersion of unmodified and organically modified montmorillonite (MMT) clay into poly(2,6-dimethyl phenylene oxide)/polystyrene miscible blend in the range of 2-10 wt% clay were investigated by wide-angle x-ray diffraction, transmission electron microscopy, differential scanning calorimetry, thermogravimetric analysis and tensile mechanical tests. The systems based on unmodified sodium MMT (Na+MMT) as well as Cloisite 20A, Cloisite 30B and Cloisite 10A organically modified clays showed polymer intercalation. The glass transition temperature (T-g) value was not affected by the volume fraction of clay and chemical nature of the organoclay. The thermal degradation stability of nanocomposites is found to be only slightly better than that of the blend matrix. A percolation threshold of around 4 wt% organoclay loading is observed. An improvement of 35% relative to unfilled polymer blend matrix is observed for the modulus, for Cloisite 20A nanocomposite containing 2 wt% organoclay. The observed modulus improvement with significant retention of elongational tensile strength and tensile ductility in case of unmodified Na-MMT and Cloisite 30B nanocomposites appears promising. The modulus prediction using Halpin-Tsai model is found to be closer to the experimental data when MMT volume fraction rather than the organoclay volume fraction is used.
Keywords: filler; interface; interphase; mechanical properties; Nanostructures; Polymer-matrix composites

Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

Acid-base cooperative catalysis over mesoporous nitrogen-rich carbon - Goyal, Reena; Sarkar, Bipul; Lucas, Nishita; Bordoloi, Ankur (ChemCatChem, 2014)
WOx nanoclusters (2-3 nm) embedded on a mesoporous nitrogen-rich carbon material were synthesized by using novel methodology. This material was very effectively capitalized as a new carbon-based acid-base cooperative catalyst for sequential acetal hydrolysis and Knoevenagel condensation reactions. The protocol was also explored for the nitroaldol condensation reaction.
Keywords: cooperative catalysts; Knoevenagel condensation; mesoporous materials; Nanostructures; nitro aldol reaction

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Novel precursors for anatase nanorods and their application in DSSCs - Mishra, Biswajit; Agarkar, Shruti A.; Khushalani, Deepa (Materials Chemistry and Physics, 2014)
Syntheses for the formation of two new precursors for TiO2 nanorods: titanium propanediolate and titanium erythritolate, have been detailed. These precursors have a rod like morphology and have been found to have higher thermal stability than commercially available precursors. The conversion of the precursors to anatase phase of TiO2 involves a simple heating protocol and importantly the morphology is conserved. The resulting anatase nanorods have been characterised and evaluated as photoanodes in dye sensitized solar cells (DSSCs). Overall device efficiencies of 3.2% and 2.3% were achieved when anatase rods (obtained from titanium propanediolate and titanium erythritolate respectively) were used. These values are higher than the 1.1% efficiency obtained from the control device (made with spherical anatase nanoparticles). It is found that forming ordered 1-D rods leads to enhanced charge transport and charge collection at the electrode along with a commensurate decrease in charge recombination. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Inorganic compounds; Nanostructures; Non-crystalline materials; Sol-gel growth

Synthesis and luminescence of graphene-nano calcium sulphide composite - Sharma, Geeta; Patil, K. R.; Gosavi, S. W. (Materials Chemistry and Physics, 2014)
Graphene-nanocrystalline calcium sulphide has been synthesized using in-situ reduction of calcium salt and graphene oxide. Graphene oxide was prepared using Hummer's method. Surface morphology and crystal structure of samples were observed by transmission electron microscopy (TEM) and X-Ray diffraction (XRD). Ultra thin graphene and graphene oxide sheets with size ranging between tens to several hundreds of square nanometers are observed in TEM images. The TEM micrographs of G-CaS show that CaS particles are embedded in graphene sheets and the average particle size of CaS particles in the composite is less than 50 nm. The reduction in the intensity of various functional groups in FTIR spectrum also confirms the formation of graphene. The UV-Visible spectra of CaS shows absorption peak at 220 nm with a small shoulder at 250 nm whereas in G-CaS 220 nm absorption peak has reduced intensity and the shoulder at 250 nm has now shifted to 270 nm due to modification in the defect structure of CaS by graphene. CaS and G-CaS shows photoluminescence emission at 470 nm (lambda(exc.) = 375 nm) and 440 nm (lambda(exc.) = 350 nm) respectively, however emission intensity of G-CaS is relatively lower than CaS. Although the emission intensity is found to be lower than CaS, addition of CaS to graphene in G-CaS complex has made graphene luminescent. XPS spectra also indicate reduction of various oxygen containing functional groups in highly reduced graphene oxide and G-CaS. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanostructures; powder diffraction; Precipitation

Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten

Microwave-assisted synthesis of few-layered TaTe2 and its application as supercapacitor - Chakravarty, Disha; Kumar, Praveen; Ugale, Vaishali S.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report a simple and rapid microwave-assisted synthesis of tantalum telluride (TaTe2) nanosheets. The ratio of tantalum pentachloride (TaCl5) and elemental tellurium (Te) powder were adjusted in the presence of NaBH4 in such a way as to obtain the TaTe2 nanosheet. The samples were characterized by various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and XRD. Our SEM, TEM, and AFM results show the formation of sheet-like morphology, while the XRD data confirms the high crystalline quality and stable phase of the TaTe2 formed. The supercapacitor cells were fabricated by using TaTe2 nanosheets as anode material, platinum metal wire as a counterelectrode, and Ag/AgCl as reference electrode. The calculated coulombic efficiency is more than 95%, while the cycle-to-cycle decrease in capacity is less than 5%. The maximum discharge or charging capacity is below 2.4 Wh/kg, which is an ideal characteristic for achieving supercapacitor behavior.
Keywords: Microwave chemistry; Nanostructures; Supercapacitors; Tantalum; Tellurium

SBA-15-oxynitrides as a solid-base catalyst: effect of nitridation temperature on catalytic activity - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, Chinnakonda S.; Madhu, Perunthiruthy K.; Polshettiwar, Vivek (Angewandte Chemie-International Edition, 2015)
Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.
Keywords: heterogeneous catalysis; Nanostructures; NMR spectroscopy; photoelectron spectroscopy; solid-state structures

Self-assembled vertically aligned gold nanorod super-lattices for ultra-high sensitive detection of molecules - Apte, Amey; Bhaskar, Prashant; Das, Raja; Chaturvedi, Smita; Poddar, Pankaj; Kulkarni, Sulabha (Nano Research, 2015)
We show that self-assembled vertically aligned gold nanorod (VA-GNRs) superlattices can serve as probes or substrates for ultra-high sensitive detection of various molecules. D-glucose and 2,4,6-trinitrotoluene (TNT) have been chosen as model systems due to their very low Raman cross-sections (5.6 x 10(-30) cm(2).molecule(-1).sr(-1) for D-glucose and 4.9 x 10(-31) cm(2). molecule(-1).sr(-1) for TNT) to show that the VA-GNR superlattice assembly offers as low as yoctomole sensitivity. Our experiment on mixed samples of bovine serum albumin (BSA) and D-glucose solutions demonstrate sensitivity for the latter, and the possible extension to real samples. Self-assembled superlattices of VA-GNRs were achieved on a silicon wafer by depositing a drop of solvent containing the GNRs and subsequent solvent evaporation in ambient conditions. An additional advantage of the VA-GNR monolayers is their extremely high reproducible morphology accompanied by ultrahigh sensitivity which will be useful in many fields where a very small amount of analyte is available. Moreover the assembly can be reused a number of times after removing the already present molecules. The method of obtaining VA-GNRs is simple, inexpensive and reproducible. With the help of simulations of monolayers and multilayers it has been shown that superlattices can achieve better sensitivity than monolayer assembly of VA-GNRs.
Keywords: Nanostructures; Raman spectroscopy; self-assemblies; sensors; superlattices

Photocatalytic degradation of methylene blue on Sn-doped titania nanoparticles synthesized by solution combustion route - Bhange, P. D.; Awate, S. V.; Gholap, Ramkrishna S.; Gokavi, G. S.; Bhange, Deu S. (Materials Research Bulletin, 2016)
Series of tin-doped titania nanoparticles with varying tin content in the range 0-20 mol% have been prepared by solution combustion synthesis route using urea as a fuel. The structure, surface morphology and optical activity of Sn-doped TiO2 nanoparticles were investigated by various analytical techniques such as powder XRD, SEM, TEM, UV-vis and N-2 adsorption study. The crystalline structures of the various phases were studied by rietveld refinement of the XRD data. The photocatalytic performance of Sn-doped titania nanoparticles were tested for degradation of MB under UV and visible light irradiation. The results reveal that the photocatalytic activity increases with increase in tin content which may be due to decrease in crystallite size with increase in surface area. The doping of Sn into TiO2 lattice hinders the recombination of electrons and holes thus enhance the quantum efficiency of photocatalytic reaction. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; composites; Nanostructures; X-ray diffraction

Synthesis and self-assembly of dumbbell shaped ZnO sub-micron structures using low temperature chemical bath deposition technique - Borade, P.; Joshi, K. U.; Gokarna, A.; Lerondel, G.; Walke, P.; Late, Dattatray J.; Jejurikar, S. M. (Materials Chemistry and Physics, 2016)
We report well dispersed horizontal growth of ZnO sub-micron structures using simplest technique ever known i.e. chemical bath deposition (CBD). A set of samples were prepared under two different cases A) dumbbell shaped ZnO grown in CBD bath and B) tubular ZnO structures evolved from dumbbell shaped structures by dissolution mechanism. Single phase wurtzite ZnO formation is confirmed using X-ray diffraction (XRD) technique in both cases. From the morphological investigations performed using scanning electron microscopy (SEM), sample prepared under case A indicate formation of hex bit tool (HBT) shaped ZnO crystals, which observed to self-organize to form dumbbell structures. Further these microstructures are then converted into tubular structures as a fragment of post CBD process. The possible mechanism responsible for the self-assembly of HBT units to form dumbbell structures is discussed. Observed free excitonic peak located at 370 nm in photoluminescence (PL) spectra recorded at 18 K indicate that the micro/nanostructures synthesized using CBD are of high optical quality. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy (STEM; Microstructure; Nanostructures; Optical properties; Photoluminescence spectroscopy; Raman spectroscopy and scattering; TEM and SEM)

Ultrananocrystalline diamond decoration on to the single wall carbon nano tubes - Sinha, B.; Late, D.; Jejurikar, S.M. (Applied Surface Science, 2017)
We have demonstrated the decoration of the ultrananocrystalline diamonds on single walled carbon nanotubes using a hot filament assisted chemical vapor deposition. Study reveals the critical influence of the filament to substrate distance on the formation of ultrananocrystalline diamonds on to the single walled carbon nanotubes. It is also observed that etching of carbon nanotubes, due to the presence of unavoidable atomic hydrogen throughout the chemical vapor deposition processes, can be significantly reduced by adjusting the filament to substrate distance. Morphological and structural investigations performed using high resolution transmission electron microscope suggests the growth of ultrananocrystalline diamond is subsequent to the formation of crystalline sp2 carbon layer on the nanotube wall, enabling us to suggest a growth model. The composite synthesized can be thought not only to use as a fuel cell catalyst support but also as chemical sensors, bio-sensors and micro electromechanical systems (MEMS).
Keywords: Carbon nanotubes; Composite Coating; Electron microscopy (STEM; Nanostructures; TEM and SEM)

Selective oxidation of cyclohexane to cyclohexanone using chromium oxide supported mesoporous MCM-41 nanospheres: probing the nature of catalytically active chromium sites - Betsy, Kurisingal J.; Nayak, Chandrani; Lazar, Anish; Krishnan, Athira; Bhattacharyya, Dibyendu; Jha, Shambhu N.; Vinod, Chathakudath P. (ChemCatChem, 2018)
Highly dispersed chromium oxide supported mesoporous MCM-41 nanosphere catalysts have been synthesized using a simple wet impregnation method. This work is devoted to a systematic study to reveal the active Cr sites in chromium oxide supported MCM-41 nanosphere catalysts for the selective oxidation of cyclohexane to cyclohexanone. To probe the nature of the active species, we synthesized 0.5-10wt% Cr loaded catalysts and characterized them by using XRD, UV/Vis spectroscopy, Raman spectroscopy, X-ray photoelectron spectroscopy, extended X-ray absorption fine structure analysis, X-ray absorption near edge structure analysis, N-2 sorption analysis, FTIR spectroscopy, (SiNMR)-Si-29 spectroscopy, SEM, and TEM. The liquid-phase oxidation of cyclohexane to cyclohexanone (99% selectivity) was performed under mild reaction conditions, and the results reveal clearly that the 5wt% Cr loaded catalyst was optimum for the reaction. The initial composition of isolated Cr3+ species in the catalyst is the major factor that influences the enhanced activity for cyclohexane oxidation.
Keywords: chromium; heterogeneous catalysis; Nanostructures; Oxidation; supported catalysts

Cadmium sulfide nanostructures: influence of morphology on the photocatalytic degradation of erioglaucine and hydrogen generation - Shenoy, Sulakshana; Jang, Eunyong; Park, Tae Joo; Gopinath, Chinnakonda S.; Sridharan, Kishore (Applied Surface Science, 2019)
Size and shape of inorganic materials are known to have great effects on their physical and chemical properties. Here, for the first time we report the visible light driven photocatalytic degradation of erioglaucine - a stable organic dye molecule in the presence of chemically synthesized nanoscale CdS with 1D (nanorods), 2D (nanosheets) and 3D (hierarchical) morphology. Visible light driven photocatalytic degradation efficiency of both 1D and 3D CdS in the removal of erioglaucine are identical. Surprisingly, with 5 min of sonication, the highly crystalline 3D CdS stacked with many thin nanowires containing numerous active surface sites exhibited fourfold enhanced photodegradation efficiency in comparison to 1D and 2D CdS. Scavenger studies revealed that electrons and superoxide radicals are primary reactive species involved in the photodegradation of erioglaucine, while cyclic photodegradation studies revealed the good stability of 3D CdS against photocorrosion. Further, the photocatalytic hydrogen evolution studies also revealed the excellent activity of 3D CdS in comparison to 1D and 2D CdS. Thus, we find that the morphology indeed influences the photocatalytic activity. These results reveal that 3D CdS nanostructures investigated in the present work are efficient photocatalysts that could be fine-tuned for both environmental remediation and hydrogen generation applications.
Keywords: Cadmium sulfide; Erioglaucine; Hydrogen evolution; Nanostructures; Photocatalysis

Boron nitride and oxide supported on dendritic fibrous nanosilica for catalytic oxidative dehydrogenation of propane - Belgamwar, Rajesh; Rankin, Andrew G. M.; Maity, Ayan; Mishra, Amit Kumar; Gomez, Jennifer S.; Trebosc, Julien; Vinod, Chathakudath P.; Lafon, Olivier; Polshettiwar, Vivek (ACS Sustainable Chemistry & Engineering, 2020)
In this work, we were able to significantly increase the activity of boron nitride (BN) catalysts used for the oxidative dehydrogenation (ODH) of propane by designing and synthesizing BN supported on dendritic fibrous nanosilica (DFNS). DFNS/BN showed a markedly increased catalytic efficiency, accompanied by exceptional stability and selectivity. Textural characterization, together with solid-state nuclear magnetic resonance (NMR) and X-ray photoelectron spectroscopic analyses, indicates the presence of a combination of unique fibrous morphology of DFNS and various boron sites connected to silica to be the reason for this increase in the catalytic performance. Notably, DFNS/B2O3 also showed catalytic activity, although with more moderate selectivity compared to that of DFNS/BN. Solid-state NMR spectra indicate that the higher selectivity of DFNS/BN might stem from a larger amount of hydrogen-bonded hydroxyl groups attached to B atoms. This study indicates that both boron nitride and oxide are active catalysts and by using high surface area support (DFNS), conversion from propane to propene as well as productivity of olefins was significantly increased.
Keywords: Electron microscopy; heterogeneous catalysis; Nanostructures; NMR spectroscopy; propane dehydrogenation; X-ray diffraction; X-ray photoelectron spectroscopy

Inhibition of quorum sensing, motility and biofilm formation ofpseudomonas aeruginosaby copper oxide nanostructures - Desai, Dnyanada G.; Swarali, H.; Navale, Govinda R.; Prabhune, A.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Cluster Science, 2020)
Quorum sensing (QS) is the communication between bacterial cells governed by their population density and regulated by the genes controlling virulence factors and biofilm formation. Multiple mechanisms of biofilms are resistive to antimicrobial chemotherapy; therefore novel strategies are required to overcome its limitations. Here, we report the effect of various copper oxide nanostructures (CuO-NSs) on quorum sensing inhibition. The two-dimensional CuO-NSs such as interlaced nanodiscs, nanodiscs and leaf-shaped nanosheets are prepared via a simple chemical method. The Quorum sensing inhibition (QSI) activity of all the CuO-NS are examined using reporter strainChromobacterium violaceumCV026 andEscherichia colipSB1142. We found that the CuO-interlaced nanodisc structures exhibit better QSI activity than nanodiscs and leaf-shaped sheets. The interlaced nanodisc structures are inhibited various long-chainN-acyl homoserine lactones (AHLs) mediated QS individually and confirmed by other QS-associated phenomena forPseudomonas aeruginosa, including biofilm inhibition, inhibition of virulence factors such as pyocyanin, protease production and swarming motility. Thus QSI activity of CuO-NSs is solely dependent on specific shape offering large surface area and more active sites. The CuO-NS is effective quorum sensing inhibitors, which has potential clinical applications in the management ofP. aeruginosaassociated infections.
Keywords: aeruginosa; Biofilm; Nanostructures; P; quorum sensing; Virulence factors